Williamson-hall analysis and absorption spectrum fitting in the estimation of crystallite size and band gap energy of CdZnS thin films - O. O. Olasanmi; A. I. Mukolu (Recent Advances in Natural Sciences, 2024)
CdZnS ternary thin film was successfully prepared from cadmium sulphide (CdS)/zinc sulphide (ZnS) bilayer and its subsequent post thermal annealing via chemical bath technique. X-ray diffraction measurement indicates that the samples presented a crystalline wurtzite phase with (002) plane as the preferred orientation. Williamson-Hall (W-H) analysis was employed to estimate the crystallite size and the microstrain. The result showed that the crystallite size decreases with increasing ZnS layer deposition times. Using the Tauc model, the absorption spectrum fitting (ASF) procedure was used to determine the optical band gap energy. The values of the band gap energy range between 3.61 and 3.66 eV, with the values increasing with ZnS layer deposition times.